New insights from small rhythmic circuits. (October 2022) - Marder, Eve; Kedia, Sonal; Morozova, Ekaterina O.
Abstract: Small rhythmic circuits, such as those found in invertebrates, have provided fundamental insights into how circuit dynamics depend on individual neuronal and synaptic properties. Degenerate circuits are those with different network parameters and similar behavior. New work on degenerate circuits and their modulation illustrates some of the rules that help maintain stable and robust circuit function despite environmental perturbations. Advances in neuropeptide isolation and identification provide enhanced understanding of the neuromodulation of circuits for behavior. The advent of molecular studies of mRNA expression provides new insight into animal-to-animal variability and the homeostatic regulation of excitability in neurons and networks. Highlights: Half-center oscillator responses vary with their underlying mechanism. Environmental perturbations reveal differential robustness in degenerate circuits. Large isoform families of biologically active neuropeptides reconfigure circuits. mRNA correlations in identified cells show activity-dependent changes. Neuromodulation allows networks to be flexible and stable.